IMPLEMENTASI SISTEM PENGATURAN LAMPU PADA INKUBATOR TELUR AYAM MENGGUNAKAN SENSOR DHT 11 DAN ARDUINO UNO R3: Sistem Irigasi Otomatis untuk Budidaya Kecambah Kaya Nutrisi Menggunakan Arduino Uno - Atmiasri, Atmiasri; wildan surya wijaya; Mochamad Choirul, Fu'ad (Universitas PGRI Adi Buana Surabaya, 2024)
This research develops a prototype of a lamp setting system in a chicken incubator using DHT11 and Arduino Uno R3 sensors. The purpose of this system is to control the temperature and humidity inside the incubator automatically to create optimal conditions for hatching chicken eggs. The DHT11 sensor serves to measure temperature and humidity, while the Arduino Uno R3 is used as a microcontroller that processes data and regulates the heating lamp. This system works by comparing the sensor measurement results with a set setpoint value. If the temperature or humidity is outside the desired limits, the Arduino will turn the heating light on or off to return the ambient conditions to the optimal range. Tests show that this system is effective in maintaining the appropriate temperature and humidity, thus increasing the success rate of hatching chicken eggs. The results of this study show that the prototype developed can be a practical and efficient solution for the process of hatching chicken eggs.